2009
DOI: 10.1590/s1413-81232009000500007
|View full text |Cite
|
Sign up to set email alerts
|

Atendimentos de emergência por acidentes na Rede de Vigilância de Violências e Acidentes: Brasil, 2006

Abstract: Resumo Em 2006, o Ministério da Saúde implantou a Rede de Serviços Sentinelas de Vigilância de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
1
32

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 18 publications
7
14
1
32
Order By: Relevance
“…The low representation of work accidents among the external causes and prevalence of commuting accidents were revealed in this study, whose results differ from findings of other publications which had the object of investigation work accidents attended at other levels of health care the example of emergency [8][9][10]23 . As noted by Conceição et al 8 , in the main emergency department in Salvador (BA), occupational accidents accounted for 31.6% of external causes, and of these, 77.9% could be classified as typical accidents.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The low representation of work accidents among the external causes and prevalence of commuting accidents were revealed in this study, whose results differ from findings of other publications which had the object of investigation work accidents attended at other levels of health care the example of emergency [8][9][10]23 . As noted by Conceição et al 8 , in the main emergency department in Salvador (BA), occupational accidents accounted for 31.6% of external causes, and of these, 77.9% could be classified as typical accidents.…”
Section: Discussioncontrasting
confidence: 99%
“…As noted by Conceição et al 8 , in the main emergency department in Salvador (BA), occupational accidents accounted for 31.6% of external causes, and of these, 77.9% could be classified as typical accidents. This divergence can be explained assuming that these hospitalizations correspond to the most severe cases 23 , and the set of events that causes them cannot be similar to that found in other levels of service delivery.…”
Section: Discussionmentioning
confidence: 95%
“…Among the features of the event, this study showed that public roads and homes were the main places of occurrence of accidents, especially among women, while other locations prevail in men, included therein bars or similar and commercial establishments. These data confirm findings of the 2006 32 Although little more than a third of the victims has informed that the accident was work-related and that a small part was involved in the use of alcohol, it is important to highlight the issue of alcoholism among indigenous as an aggravating factor to the overall health and accidents in particular. However, information about the use of alcohol and safety equipment such as helmets are underestimated, given that users can evade them and the record of such data has been little or inadequately completed.…”
Section: Discussionsupporting
confidence: 78%
“…We observed that a considerable share (37.1%) of indigenous treated has 10 or more schooling years. This percentage is similar to all persons attended due to accidents in the 2006 and 2009 VIVA surveys, in which high proportions of people with more schooling years were also observed 32,33 . Falls and traffic accidents involving mainly motorcycles led the indigenous to seek more care at a health facility.…”
Section: Discussionsupporting
confidence: 74%
“…Brazil has innovated epidemiological surveys 9 , such as household surveys (e.g. the National Health Survey -PNS) 10 , telephone surveys 11 , surveys with teenagers 12 , surveys in emergency rooms 13 , longitudinal follow-up studies 14 , among others. Furthermore, the information obtained through surveys complements the knowledge of health inequalities, supporting policies, to achieve greater equity 4,15,16 .…”
Section: Introductionmentioning
confidence: 99%